Anti-depressant use during pregnancy in Australia: findings from the Longitudinal Study of Australian Children - Lewis, A; Galbally, M; Bailey, C (My University, 2012)
Increasing awareness among health professionals and detection of antenatal and postnatal depression has resulted in sharp increases in the prescription of anti-depressant medication in pregnancy. The literature on effects on the newborn of antenatal anti-depressant exposure raises a number of questions about the safety of such prescription practices including findings of increased birth complications, lower gestational age and lowered birth weights resulting from prenatal exposure. This letter aims to provide information on the prevalence of anti-depressant use in Australia and the characteristics of mothers who take anti-depressants during pregnancy.
Keywords: Children -- Babies; Health -- Medications; Life Events -- Birth/adoption; Health and wellbeing; Disadvantage, adversity and resilience; Health; Children; Life Events; Babies; Birth/adoption; Medications; Dsiadvantage, adversity and resilience; Health and wellbeing; Adversity and resilience